New insights into sugar characterization in complex plant matrices by high-performance thin-layer chromatography. Issue 13 (8th August 2016) - De Lucia, Daniela; Manfredini, Stefano; Vertuani, Silvia; Bernardi, Tatiana
ABSTRACT: High-performance thin-layer chromatography (HPTLC) is an innovative, green, reliable, and rapid method for the characterization of complex sugar mixtures. For research into sustainable nontimber forest products, Adansonia digitata dry fruit pulp in this proof-of-concept study was used to demonstrate this method due to its reported high nutritional value and prebiotic activity. Chromatographic separations were performed on (20 × 10 cm 2 ) HPTLC glass plates with diol stationary phase, using a 15-step gradient by mixing solutions acetone/acetonitrile 1:1, and ultrapure water for enzymatic degradation products. Instead, monosaccharide moieties were separated on HPTLC silica gel 60 F254 over isocratic mode with 80 mm of eluent front composed of acetonitrile/acetic acid/water 63/33/5 v/v/v. Identification and quantification were performed by densitometry acquisitions at 400 nm after opportune derivatization. Our research highlighted that this technique can be used as a standard method to gain new insights into inulin determinations, with several advantages over existing conventional liquid chromatography. The development of innovative methods for the characterization of biopolymers is crucial, for food and nutraceutical industry and for quality control of phytochemicals. Characterization of such materials, up until now, has been done by mass difference and so accurate analytical methods were lacking. GRAPHICAL ABSTRACT: